Effectiveness and Waning of Protection With Different SARS-CoV-2 Primary and Booster Vaccines During the Delta Pandemic Wave in 2021 in Hungary (HUN-VE 3 Study) - Vokó, Zoltán; Kiss, Zoltán; Surján, György; Surján, Orsolya; Barcza, Zsófia; Wittmann, István; Molnár, Gergő Attila; Nagy, Dávid; Müller, Veronika; Bogos, Krisztina; Nagy, Péter; Kenessey, István; et al. (Frontiers in Immunology, 2022)
Background: In late 2021, the pandemic wave was dominated by the Delta SARS-CoV-2 variant in Hungary. Booster vaccines were offered starting from August 2021. Methods: The nationwide HUN-VE 3 study examined the effectiveness and durability of primary immunization and single booster vaccinations on SARS-CoV-2-related infection, hospitalization and mortality during the Delta wave. Results: The study population included 8,087,988 individuals aged 18–100 years at the beginning of the pandemic. During the Delta wave, after adjusting for age, sex, calendar day, and chronic diseases, vaccine effectiveness (VE) of primary vaccination against registered SARS-CoV-2 infection was between 11% to 77% and 18% to 79% 14–120 days after primary immunization in the 16–64 and 65–100 years age cohort respectively, while it decreased to close to zero in the younger age group and around 40% or somewhat less in the elderly after 6 months for almost all vaccine types. In the population aged 65–100 years, we found high, 88.1%–92.5% adjusted effectiveness against Covid-19 infection after the Pfizer-BioNTech, and 92.2%–95.6% after the Moderna booster dose, while Sinopharm and Janssen booster doses provided 26.5%–75.3% and 72.9%–100.0% adjusted VE, respectively. Adjusted VE against Covid-19 related hospitalization was high within 14–120 days for Pfizer-BioNTech: 76.6%, Moderna: 83.8%, Sputnik-V: 78.3%, AstraZeneca: 73.8%, while modest for Sinopharm: 45.7% and Janssen: 26.4%. The waning of protection against Covid-19 related hospitalization was modest and booster vaccination with mRNA vaccines or the Janssen vaccine increased adjusted VE up to almost 100%, while the Sinopharm booster dose proved to be less effective. VE against Covid-19 related death after primary immunization was high or moderate: for Pfizer-BioNTech: 81.5%, Moderna: 93.2%, Sputnik-V: 100.0%, AstraZeneca: 84.8%, Sinopharm: 58.6%, Janssen: 53.3%). VE against this outcome also showed moderate decline over time, while booster vaccines restored effectiveness up to almost 100%, except for the Sinopharm booster. Conclusions: The HUN-VE 3 study demonstrated waning VE with all vaccine types for all examined outcomes during the Delta wave and confirmed the outstanding benefit of booster vaccination with the mRNA or Janssen vaccines. This is the first study to provide comparable effectiveness results for six different booster types during the Delta pandemic wave.